2011
DOI: 10.3356/jrr-10-92.1
|View full text |Cite
|
Sign up to set email alerts
|

Home-Range Size and Territorial Calling of Southern Boobooks (Ninox novaeseelandiae) in Adjacent Territories

Abstract: There is disagreement about whether Southern Boobooks Ninox novaeseelandiae duet. A recent review of the species concluded that duetting does occur, based on (i) observations of captives and (ii) two reports from wild birds, including one from New Zealand. We examined definitions of duetting, and attempted to collect evidence for it in the calling behaviour of three mated pairs on adjacent territories observed from October 1996 to October 1999. To identify callers, six adults were colour-marked, and four of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…These findings support previous studies by Olsen et al (2002), who found that calling behaviour varied with season, although their study used unsolicited calling behaviour to establish occupancy. This seasonality to responsiveness may reflect the species' breeding cycle, during which individuals may display more territorial behaviour (Olsen et al 2011). Similar observations have been made for the ferruginous pygmy-owl (Glaucidium brasilianum cactorum), for which detectability during the breeding season approached 100% (Flesch and Steidl 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These findings support previous studies by Olsen et al (2002), who found that calling behaviour varied with season, although their study used unsolicited calling behaviour to establish occupancy. This seasonality to responsiveness may reflect the species' breeding cycle, during which individuals may display more territorial behaviour (Olsen et al 2011). Similar observations have been made for the ferruginous pygmy-owl (Glaucidium brasilianum cactorum), for which detectability during the breeding season approached 100% (Flesch and Steidl 2007).…”
Section: Discussionmentioning
confidence: 99%
“…CHPs can also have “holes” and be composed of disjoint polygons, which can accommodate distribution patterns of animals that avoid certain areas. CHP are fairly robust to sample size variations and to inhomogeneous point distributions [ 51 ] and do not overestimate areas of use like MCP [ 52 , 148 ]. However, they perform relatively worse when home ranges have a concave, or convex shape compared to linear, disjoint or perforated, but this could be related to the process of removing triangles [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite its advantages, CHP are not as studied and frequently used as MCP [ 52 , 165 ]. The Delaunay triangulation required for producing CHP can be implemented in many GIS softwares [ 52 , 57 ], such as standard functions in ArcGIS 5 (ESRI, Inc., requires subscription purchase) e.g., [ 51 , 148 ] and also QGIS 6 (free and open-source). In the former, the hot spot analysis with rendering spatial statistical tool can be used as a more objective way of selecting triangles [ 112 ].…”
Section: Methodsmentioning
confidence: 99%
“…Birds therefore have to occupy a large enough territory to provide foraging in high and low food productivity years. Olsen et al (2002Olsen et al ( , 2011 calculated home ranges of between 70.6 and 205.8 ha (MCP = 100%) for southern boobook (Ninox novaeseelandiae) in urban areas of Canberra, Australia. It is possible that these birds have to range further for suitable habitat and food in a modified urban setting.…”
Section: Discussionmentioning
confidence: 99%